PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK DUA TINGGAL DUA TAMU TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 4 TARUSAN KABUPATEN PESISIR SELATAN TAHUN PELAJARAN 2013/2014 - Syafrina, Gusnia; Rahmi, Rahmi; Harisman, Yulyanti (STKIP PGRI Sumbar, 2013)
The background of the research is comprehension about math concept for the students grade VIII at SMPN 4 Tarusan Kabupaten Pesisir Selatan. The purpose of the research to know which the comprehension math concept by used technique Two Stay Two Stray be better than the comprehance math concept by used konvensional learning for students at VIII SMPN 4 Tarusan Kabupaten Pesisir Selatan. Type of study was experimental research by random designed on the subject. The instrument of this research is essay, with reabilition is 0,90. The result of hypothesis test obtained P-Value = 0,000 is less than Î± = 0,05. Based on data description and hypothesis tests can be concluded that conceptual mathematic students comprehension by applying cooperative teaching model in using Two Stay Two Strayâs technique is better than conceptual mathematic students in conventional learning.